Differential evolution of peripheral cytokine levels in symptomatic and asymptomatic responses to experimental influenza virus challenge. (16th December 2015) - McClain, M. T.; Henao, R.; Williams, J.; Nicholson, B.; Veldman, T.; Hudson, L.; Tsalik, E. L.; Lambkin‐Williams, R.; Gilbert, A.; Mann, A.; Ginsburg, G. S.; Woods, C. W.
Summary: Exposure to influenza virus triggers a complex cascade of events in the human host. In order to understand more clearly the evolution of this intricate response over time, human volunteers were inoculated with influenza A/Wisconsin/67/2005 (H3N2), and then had serial peripheral blood samples drawn and tested for the presence of 25 major human cytokines. Nine of 17 (53%) inoculated subjects developed symptomatic influenza infection. Individuals who will go on to become symptomatic demonstrate increased circulating levels of interleukin (IL)‐6, IL‐8, IL‐15, monocyte chemotactic protein (MCP)‐1 and interferon (IFN) gamma‐induced protein (IP)‐10 as early as 12–29 h post‐inoculation (during the presymptomatic phase), whereas challenged patients who remain asymptomatic do not. Overall, the immunological pathways of leucocyte recruitment, Toll‐like receptor (TLR)‐signalling, innate anti‐viral immunity and fever production are all over‐represented in symptomatic individuals very early in disease, but are also dynamic and evolve continuously over time. Comparison with simultaneous peripheral blood genomics demonstrates that some inflammatory mediators (MCP‐1, IP‐10, IL‐15) are being expressed actively in circulating cells, while others (IL‐6, IL‐8, IFN‐α and IFN‐γ) are probable effectors produced locally at the site of infection. Interestingly, asymptomatic exposed subjects are not quiescent either immunologically or genomically, but instead exhibit early and persistent down‐regulation of important inflammatory mediators in the periphery. The host inflammatory response to influenza infection is variable but robust, and evolves over time. These results offer critical insight into pathways driving influenza‐related symptomatology and offer the potential to contribute to early detection and differentiation of infected hosts.